Microenvironment-Cell Nucleus Relationship in the Context of Oxidative Stress - Chittiboyina, Shirisha; Bai, Yunfeng; Lelièvre, Sophie A. (Frontiers in Cell and Developmental Biology, 2018)
The microenvironment is a source of reactive oxygen species (ROS) that influence cell phenotype and tissue homeostasis. The impact of ROS on redox pathways as well as directly on epigenetic mechanisms and the DNA illustrate communication with the cell nucleus. Changes in gene transcription related to redox conditions also influence the content and structure of the extracellular matrix. However, the importance of microenvironmental ROS for normal progression through life and disease development still needs to be thoroughly understood. We illustrate how different ROS concentration levels trigger various intracellular pathways linked to nuclear functions and determine processes necessary for the differentiation of stem cells. The abnormal predominance of ROS that leads to oxidative stress is emphasized in light of its impact on aging and diseases related to aging. These phenomena are discussed in the context of the possible contribution of extracellular ROS via direct diffusion into cells responsible for organ function, but also via an impact on stromal cells that triggers extracellular modifications and influences mechanotransduction. Finally, we argue that organs-on-a-chip with controlled microenvironmental conditions can help thoroughly grasp whether ROS production is readily a cause or a consequence of certain disorders, and better understand the concentration levels of extracellular ROS that are necessary to induce a switch in phenotype.